Implementasi Pola Komunikasi dalam Membentuk Kohesivitas di Organisasi Kemahasiswaan - Pradipta, William; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This study examines the patterns of communication that occur in an organization in order to build solidarity. Researchers took a study at the Student Executive Board of the Faculty of Communication Sciences, Padjadjaran University. The methodology used is a qualitative methodology with data collection techniques through interviews, observation, and documentation collected by researchers. The theories used are organizational communication theory, leadership communication, communication patterns, and solidarity. After conducting the research, the researcher concluded that the communication process at BEM Fikom Unpad took place in three stages, namely primary, which means directly face-to-face. Then secondarily, through media or digital platforms, and lastly, circularly characterized by feedback. the communication model runs in a participatory manner with openness to opinions, criticism, and suggestions and the involvement of every individual in the organization. A star-shaped or overall communication pattern that allows each individual to be a continuous communicator and communicate. The process of good communication, openness, and empathy creates the same emotional experience and close trust in one another and has an impact on building a sense of belonging and high solidarity within the organization. Penelitian ini mengupas pola komunikasi yang terjadi pada suatu organisasi dalam rangka membangun kohesivitas. Peneliti meneliti Badan Eksekutif Mahasiswa Fakultas Ilmu Komunikasi Universitas Padjajaran. Peneliti menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Teori yang digunakan adalah teori komunikasi organisasi, komunikasi kepemimpinan, pola komunikasi, dan kohesivitas. Peneliti menemukan bahwa proses komunikasi pada BEM Fikom Unpad berlangsung dalam tiga tahap, yaitu secara primer, artinya secara langsung; secara sekunder, melalui media atau platform digital; dan yang terakhir, secara sirkular ditandai dengan adanya timbal balik. Model komunikasi berjalan secara partisipatif dengan adanya keterbukaan pendapat, kritik, dan saran serta keterlibatan individu dalam organisasi. Pola komunikasi berbentuk bintang atau menyeluruh yang memungkinkan setiap individu komunikator dan komunikan. Proses komunikasi yang baik, keterbukaan, dan empati menimbulkan pengalaman emosional yang sama dan kepercayaan satu sama lain yang erat dan berimbas terbangunnya rasa memiliki dan kohesivitas organisasi yang tinggi.